Development of Interactive Multimedia-Based Learning Media for Basic Graphic Design Subjects with the ADDIE Model Guidelines at SMK Negeri 5 Malang - Husen, Dania Lazuardi; Herlambang, Admaja Dwi; Wijoyo, Satrio Hadi (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
This research aims to explain the results of the needs analysis in developing interactive multimedia-based learning media so that it can improve learning outcomes and support the learning interaction process and can motivate students during learning activities. This learning media was built by adapting the ADDIE model which consists Analysis, Design, Development, Implementation, and Evaluation phase. The results of this research test are the learning outcomes of students increase after using learning media. Hypothesis testing with Paired Sample T-Test technique produces a hypothesis that there are differences in learning outcomes due to the use of learning media. The test results based on the use of learning media by students resulted in an average eligibility of media in support of learning interactions of 85.81% and learning motivation of 87.05%. That is, learning media can be categorized as very feasible to be used to build learning interactions and learners' learning motivation.